Determination of Enterococcus faecalis and Enterococcus faecium Antimicrobial Resistance and Virulence Factors and Their Association with Clinical and Demographic Factors in Kenya. (9th November 2022) - Georges, Martin; Odoyo, Erick; Matano, Daniel; Tiria, Fredrick; Kyany'a, Cecilia; Mbwika, Daniel; Mutai, Winnie C.; Musila, Lillian
Abstract : Background . Enterococci are clinically significant because of their increasing antibiotic resistance and their ability to cause severe infections due to an arsenal of virulence genes. Few studies in the developing world have examined virulence factors that may significantly impact patient outcomes. This study describes the antimicrobial resistance profiles and prevalence of five key Enterococcal virulence genes gelE, asa, cylA, esp, and hyl in forty-four clinical Enterococcus faecalis and E. faecium isolates in Kenya and their association with patients' demographic and clinical characteristics. Results . All E. faecium isolates were obtained from hospital-acquired skin and soft tissue infections. While E. faecalis was associated with community-acquired urinary tract infections. All isolates were resistant to erythromycin, whereas 11/44 (27.5%), 25/44 (56.8%), 28/44 (63.6%), 37/44 (84.1%), 40/44 (90.0%), and 43/44 (97.5%) were susceptible to tetracycline, levofloxacin, gentamicin, ampicillin, nitrofurantoin, and teicoplanin, respectively. All isolates were susceptible to tigecycline, vancomycin, and linezolid. There was little difference in the antibiotic resistance profiles between E. faecalis and E. faecium . The prevalence of the virulence genes among the 44 isolates were 27 (61.4%) for gelE, 26 (59.1%) for asa1, 16 (36.3%) for esp, 11 (25.0%) for cylA, and 1 (2.3%) for hyl . 72.9% of E. faecalis isolates had multiple virulence genes compared to 57% of E. faecium isolates with no virulence genes. The hyl gene was only detected in E. faecium, while cylA and asa1 were only detected in E. faecalis . A significant correlation was observed between the presence of asa1 and esp virulence genes and tetracycline resistance (P = 0.0305 and 0.0363, respectively). A significant correlation was also observed between the presence of virulence genes gelE and asa1 and nitrofurantoin resistance (P = 0.0175 and 0.0225, respectively) and ampicillin resistance (P = 0.0005 and 0.0008, respectively). Conclusion . The study highlights the high levels of erythromycin resistance in E. faecalis and E. faecium, the demographic factors influencing the species distribution among patients, and the accumulation of multiple virulence genes in E. faecalis. The significant association of gelE, asa1, and esp virulence genes with drug resistance could explain the pathogenic success of E. faecalis and provides a guide for future studies.